Evaluation of CD304 expression in pediatric Blineage acute lymphoblastic leukemia - Raghda Hameed Jaseem; Subh Salim Al-Mudallal (Iraqi Journal of Cancer and Medical Genetics, 2020)
BACKGROUND: Acute lymphoblastic leukemia is the most common form of cancer (25–30%) and predominant subtype of leukemia (75–80%) in children. However, childhood ALL has considerable phenotypic and genotypic heterogeneity, which is of diagnostic and prognostic importance. CD304 is a transmembrane glycoprotein C-type lectin found on plasmacytoid dendritic cells, It acts as a receptor for class III semaphorins mediating neuronal guidance and axonal growth.Aim of the study: to study expression of CD304 in de novo newly diagnosed pediatric B- lineage ALL patients and to evaluate its association with hematological and clinical parameters.Patients and methods: This cross sectional study was conducted on 30 pediatric patients with de novo newly diagnosed BALL randomly selected in relation to sex included (16 males and 14females) with their age ranging 1-14 year.RESULTS: This study revealed that CD304 was detected in (56.67%) of newly diagnosed B-ALL patients and (43.33%) of them were negative for CD304 expression. It was detected that CD304 was not associated with age, gender, clinical presentations, other prognostic hematological parameters (Hb, WBC count, platelate count), blast percentage, NCI risk, B-ALL subtype, positive PAS and response to induction therapy.CONCLUSIONS: CD304 expression was independent on the hematological and physical characteristics of patients, since the majority of positive CD304B-ALL cases were in high risk groups of NCI criteria and 60% of non- responder were positive CD304. PAS stain was detected in standard risk groups of NCI criteria, common B-ALL subtype and response to induction therapy.